2019
DOI: 10.1039/c9ta00455f
|View full text |Cite
|
Sign up to set email alerts
|

Predictive fabrication of Ni phosphide embedded in carbon nanofibers as active and stable electrocatalysts

Abstract: With the combination of first principle calculations and thermodynamics, a predictive fabrication to modify structure and phase was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…It can be seen from the calculation results in Figure 2e that NiP 2 shows the lowest ∆G H of only −0.16 eV, which suggests the highest HER activity among the four phases. This is consistent with the experimental results [51]. Moreover, some studies have reported the influences of the crystal phase and morphology of nickel phosphides on the catalytic HER performances, which will be discussed in Part 4.1 because the studies are based on the nickel phosphide nanocrystals prepared through the solution phase method.…”
Section: Properties Of Nickel Phosphidessupporting
confidence: 89%
See 2 more Smart Citations
“…It can be seen from the calculation results in Figure 2e that NiP 2 shows the lowest ∆G H of only −0.16 eV, which suggests the highest HER activity among the four phases. This is consistent with the experimental results [51]. Moreover, some studies have reported the influences of the crystal phase and morphology of nickel phosphides on the catalytic HER performances, which will be discussed in Part 4.1 because the studies are based on the nickel phosphide nanocrystals prepared through the solution phase method.…”
Section: Properties Of Nickel Phosphidessupporting
confidence: 89%
“…Optimized surface structures for the (001) faceted Ni4P5-terminated Ni12P5, Ni3P2terminated Ni2P, Ni4P3-terminated Ni5P4, and P-terminated NiP2 (d) and corresponding free energy profiles for Pt, Ni12P5, Ni2P, Ni5P4, and NiP2 (e). Reproduced with permission from Reference [51]. The Royal Society of Chemistry, 2019.…”
Section: Properties Of Nickel Phosphidesmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, the prepared ampoule was sealed through a vacuum pump under 0.1 Torr. Finally, the sealed ampoule was thermally treated in a furnace at 500 °C for 2 hours at a ramp rate of 5 °C/min 7 .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, active electrocatalysts based on earth-abundant elements, such as transition metal compounds, have been extensively studied to replace noble metals 11,12 . Transition metal oxides 13,14 , hydroxides 15,16 , carbide 17 , nitride 18 , phosphide 19 , and sulfides 2022 have been studied as OER electrocatalysts under alkaline conditions, and transition metal sulfides 2022 , phosphides 6,7 , carbonitride 23 , and selenides 24 have been studied as HER electrocatalysts under acidic conditions. In regard to OER and HER performance, the effects of activation and optimization of electrocatalysts have recently been reported 17,18,23 .…”
Section: Introductionmentioning
confidence: 99%